An Exploration of Regional Labor Productivity Patterns of Manufacturing SMEs in Mexico - Flores, Miguel; Andrés-Rosales, Roldán; Villarreal, Amado (Journal of Reviews on Global Economics, 2016)
The goal of this paper is to characterize the small and medium-sized enterprises (SMEs) in Mexico by analyzing regional and industrial labor productivity growth differences in the manufacturing sector during the period 2004-2014. The results suggest that labor productivity differs according to the size of the establishment. While microenterprises and small establishments exhibit a moderate increase, medium- and large-sized establishments experience the largest increase during such period. The empirical analysis indicates the existence of absolute and conditional convergence in productivity growth for the SMEs. Industry differences across locations seem to be an important factor although regional differences account for the greater variation in productivity growth.